2017
DOI: 10.1038/s41598-017-08806-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Tomato CircRNAs Derived from Genes Involved in Fruit Pigment Accumulation

Abstract: 1CircRNAs, a class of widespread circular RNAs produced from precursor mRNA back-splicing, have been implicated in regulation of gene expression in eukaryotes, but their biological functions in plants have not yet been elucidated. By deep sequencing of rRNA-removed and RNase R-digested RNA samples we have identified several thousands of putative back-splicing sites in tomato fruit (Solanum lycopersicum) and show that the abundance of some of these circRNAs derived from fruit pigment biosynthesis genes are regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 49 publications
3
69
1
Order By: Relevance
“…Another one circRNA (circZDS) was transcripted from ζ-carotene desaturase (ZDS) gene, which was important for carotenoid biosynthesis [35][36][37][38]. Also, PSY1-circ1 and PDS1-circ1, respectively derived from PSY1 and PDS gene, can change fruit pigment by affect the lycopene and β-carotene accumulation in tomato [11]. All these results suggested that circRNAs could have important biological functions in the metabolite synthesis process during sea buckthorn fruit development.…”
Section: Disscusionmentioning
confidence: 96%
See 2 more Smart Citations
“…Another one circRNA (circZDS) was transcripted from ζ-carotene desaturase (ZDS) gene, which was important for carotenoid biosynthesis [35][36][37][38]. Also, PSY1-circ1 and PDS1-circ1, respectively derived from PSY1 and PDS gene, can change fruit pigment by affect the lycopene and β-carotene accumulation in tomato [11]. All these results suggested that circRNAs could have important biological functions in the metabolite synthesis process during sea buckthorn fruit development.…”
Section: Disscusionmentioning
confidence: 96%
“…A lot of fruit ripening related circRNAs were also discovered in tomato [7]. Moreover, two fruit pigment related circRNAs were verified in tomato [11]. As a medicinal and edible plant, sea buckthorn has been considered as good plant for studying the process of fruit ripening because of its continuous maturation process, abundant nourishments and availability of genome information.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that 102 target mRNAs of 39 circRNAs were involved in the pathways involved in ethylene synthesis and signal transduction (Wang et al ). The research showed that circRNA is involved in the regulation of pigment accumulation during tomato fruit ripening and overexpression of circRNA related to pigment synthesis can significantly reduce the expression level of the parental gene and the color of the response (Tan et al ). The research has found that circular RNA might play an important role in development of moso bamboo by regulating the splicing of several rapid‐growth related genes (Wang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar research found that circRNAs play an important role in the regulation and control of tomato fruits (Yin et al ). CircRNA is widely distributed in plants and has been identified in several plants such as Arabidopsis, rice, tomato and soybean using deep RNA‐seq and bioinformatic tools (Lu et al , Chen et al , Conn et al , Tan et al , Zhao et al , Zhou et al ). However, at present, comprehensive studies of circRNA in plants are lacking, and the functions of circRNA have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%